Tunable water-based metasurface for anomalous wave reflection. (1st October 2020) - Jacobsen, Rasmus E; Nielsen, Jonas Ø; Lavrinenko, Andrei V; Arslanagić, Samel
Abstract: Metasurfaces (MSs) are artificial structures which enable the full control of electromagnetic waves and they continue to be of great scientific importance. In particular, they can tailor their reflection and transmission properties by using electrically small metallic/dielectric scatterers with imprinted spatial phase variation. In the present work, we design and characterize a water-based MS with a tunable reflection at 1 GHz. The MS comprises a collection of water cylinders and we demonstrate its ability to reflect a normally incident wave at an angle of 51.3° and with a total reflection efficiency of 33%. A prototype was fabricated and is shown to exhibit an excellent agreement with the simulation results. The proposed water-based MS may serve as a cheap and bio-friendly tunable alternative for a variety of microwave communication systems.